Integration of Transcriptomic and Proteomic Approaches Reveals the Temperature-Dependent Virulence of Pseudomonas plecoglossicida - Huang, Lixing; Liu, Wenjia; Jiang, Qingling; Zuo, Yanfei; Su, Yongquan; Zhao, Lingmin; Qin, Yingxue; Yan, Qingpi (Frontiers in Cellular and Infection Microbiology, 2018)
Pseudomonas plecoglossicida is a facultative pathogen that is associated with diseases of multiple fish, mainly at 15-20 °C. Although fish disease caused by P. plecoglossicida has led to significant economic losses, the mechanisms of the temperature-dependent virulence are unclear. Here, we identify potential pathogenicity mechanisms and demonstrate the direct regulation of several virulence factors by temperature with transcriptomic and proteomic analyses, quantitative real-time PCR (qRT-PCR), RNAi, pyoverdine (PVD) quantification, the chrome azurol S (CAS) assay, growth curve measurements, a biofilm assay, and artificial infection. The principal component analysis, the heat map generation and hierarchical clustering, together with the functional annotations of the differentially expressed genes proved that, under different growth temperatures, the animation and focus of P. plecoglossicida are quite different, which may be the key to pathogenicity. Genes involved in PVD synthesis and in the type VI secretion system (T6SS) are specifically upregulated at the virulent temperature of 18 °C. Silencing of the PVD-synthesis-related genes reduces the iron acquisition, growth, biofilm formation, distribution and virulence of the bacteria. Silencing of the T6SS genes also leads to the reduction of biofilm formation, distribution and virulence. These findings reveal that temperature regulates multiple virulence mechanisms in P. plecoglossicida, especially through iron acquisition and T6SS secretion. Meanwhile, integration of transcriptomic and proteomic data provide us with a new perspective into the pathogenesis of P. plecoglossicida, which would not have been easy to catch at either the protein or mRNA differential analyses alone, thus illustrating the power of multi-omics analyses in microbiology.